The Relationship between Microalbumin Levels and HbA1c in People at Risk for Type 2 Diabetes Mellitus: Hubungan Kadar Mikroalbumin dan HbA1c pada Orang dengan Resiko Diabetes Mellitus Tipe 2 - Romli , Leo Yosdimyati (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Increased blood glucose levels in diabetes mellitus are a problem due to poor insulin synthesis, and insulin resistance conditions cause microalbumin. The purpose of this study was to determine the relationship between microalbumin levels and HbA1c in people at risk for type 2 diabetes mellitus. This type of research is a quantitative study using a cross-sectional study design. Respondents in this study were all women at risk of type 2 diabetes mellitus in the village of Ngrandulor. The research sample was taken using the purposive sampling technique, which was taken according to the criteria set by the researcher so that 28 respondents were selected. Data collection on microalbumin levels was carried out by immunoturbidimetric examination, and HbA1c was carried out by immunoassay examination. Bivariate analysis of the research data was carried out using the Spearman rank statistical test. The results showed a relationship between microalbumin levels and HbA1c in people at risk for type 2 diabetes mellitus, the p-value = 0.010. The results showed that half of the respondents had their albumin checked under microalbumin conditions, namely 14 respondents (50%) and on HbA1c examination, which showed that they were in diabetes status or conditions, namely 14 respondents (50%). This study concludes that there is a relationship between microalbumin levels and HbA1c in people at risk for type 2 diabetes mellitus, with a significance value (p) of 0.010.